Representation of Jombang as “a santri city”: landscape linguistic study - Pertiwi, Annisa; Mulyono, Mulyono (Journal of Applied Studies in Language, 2021)
This study examines the representation of Jombang district as a santri city. The purpose of this study is to describe the extent to which the representation of the mention of Jombang district as a santri city is examined from the use of language in public spaces that can reflect these nicknames. The data in this study are forty forms of language use on billboards, shop names, road signs, and general signs on other roads that can reflect the designation of Jombang district as a santri city. This is a qualitative descriptive research. The theory used is the basic theory from Landry and Bourhis (1997) which focuses on the study of landscape linguistics which refers to information functions and symbolic functions. The results showed that there were five ways of representing Jombang as a santri city, namely (1) representation through naming shops, buildings, and community groups using Arabic which was written using Latin letters, (2) representation through naming streets, alleys, and institutions using names. family or the founder of the Islamic boarding school, (3) representation through the provision of special information for the boarding school students, (4) representation through the promotion of Islamic boarding school-based schools, and (5) representation through other objects. The methods of representation are divided into six categories of language signs in public spaces, namely in the category of road signs, advertising or promotional signs, warning signs, building names, information signs, and objects. There were also factors that influenced the presence of language signs in public spaces that represented Jombang as a santri city, namely (1) being close to the boarding school area, (2) following trend which is done by other subjects around the boarding school, (3) the need for the existence of an institution, and (4) information facilities for the general public.